Foundations : a manual for the beginning student of epistemology - Fox, Larry, 1936- (University Press of America, 1999)
Foundations: A Manual for the Beginning Student of Epistemology provides the tools required for understanding traditional western epistemology, and an appreciation for its development into contemporary theories without using the traditional historic approach. Instead of requiring students to struggle through a myriad of epistemological works, each with its own unique perspective, presuppositions, and terminology in hopes that they emerge with a general sense of the field, Claude L. Fox conveys the traditional concepts of western epistemology by identifying its key components and providing the student with an understanding of them. Equipped with this knowledge, students will possess the basic tools for understanding any traditional work they may study. He accomplishes this by first describing epistemology and ontology, then explaining how they constitute the field of metaphysics. Next, he examines the basic concepts of the two disciplines, concluding with the primary epistomelogical judgements and theories to which these concepts have given birth. --From publisher's description.